ChemInform Abstract: 4‐Trifluoroacetyl‐2‐phenyloxazol‐5‐one: Versatile Template for Synthesis of Trifluoromethyl‐Substituted Heterocycles. Issue 21 (27th May 2014) - Saijo, Ryosuke; Kurihara, Ken‐ichi; Kawase, Masami
Abstract Derivative (XIII) is starting material for (I) as well.